Knowledge, attitude, and practices of insulin use among type 1 diabetes patients in North India – A cross-sectional study - Manisha Gupta; Shivendra Verma; Saurabh Agarwal (Eastern Journal of Medical Sciences, 2021)
Background: Prevalence of Type 1 diabetes (T1DM) is increasing world-wide. A thorough understanding of the insulin administration including correct injection techniques, proper storage, insulin dose adjustment, meal timing, site rotation, and compliance are necessary for optimal treatment. Objective: The objective of the study was to assess knowledge, attitude, and practices (KAP) of insulin use and its effects in T1DM patients. Materials and Methods: This cross-sectional observational questionnaire-based survey was carried out among 105 T1DM patients at a tertiary care hospital during August to September 2020. A questionnaire consisting of 32 questions was formulated to assess the knowledge of diabetes, awareness of insulin use along with attitude and practices of insulin use. The responses were scored, converted into percentages, and summarized with descriptive statistics. Results: The mean scores in Knowledge, Attitude and Practices domains of KAP were 25.5±7.8, 2.6±3.9, and 8.9±1.7, respectively. We found deficiency of knowledge regarding type of insulins (31.4%), side effects of insulin (78%), and insulin injection sites (37%). Around 43% subjects had a negative attitude toward insulin and 35% were prone to use clumped insulin, 65% of subjects were aware of correct insulin injection techniques, and 77% were aware of correct insulin timing while 68.5% were aware of insulin handling during travel. Conclusion: There is an unmet need to enhance KAP domains of T1DM care and insulin administration, as the deficiencies in each domain are quite prevalent despite long term insulin use. Regular interactions with patients in the form of group meetings, patient to patient interaction and live demonstrations may alleviate fear of injection, poor compliance and incorrect techniques.